The exploration of students and teachers’ view on ecological storybooks - Nandy Intan Kurnia; Niken Anggraeni; Cindy Elsa Fitri (LITERA, 2022)
Environmental issues are on-going crises that have yet found sufficient solutions. Children, as the next generation, must be given the trust to be able to get in touch with environmental issues as form of children’s empowerment and preservation act. This study aims to describe the views of elementary school students and teachers related to children’s ecology-themed storybooks. This research is qualitative, the data collection uses a list and guided interview questions, observation sheets, questionnaire sheets, and expert validation sheets. The results of the study are as follows. First, there is a lack of ecological books in major bookstore in Yogyakarta, Indonesia. The existing children books containing environmental theme only included it as a supporting theme. This may result in most children participant to be not interested in such books.  Second, teachers are mostly in agreement as to how children ecological storybook should appear ideally. This includes realism as the story’s genre, explicit theme, forest settings, picture book form, human characters nature vs human conflict, and happy closed ending for the story. All of these are believed to be able to educate children on the on-going environmental crisis and to encourage the children to face them.Keywords: children’s storybooks, ecology, children’s empowerment, environment, children’s literature